2014
DOI: 10.1080/12460125.2014.896122
|View full text |Cite
|
Sign up to set email alerts
|

Inter-organisational coordination of H1N1 outbreak: data collection, and analyses of a pilot field study

Abstract: Inter-organisational coordination data collection and analyses of H1N1 outbreak: A pilot field studyImproving effectiveness in response to H1N1 outbreaks requires us to understand how different organisations within the outbreak coordination network work collectively to share information needed to operate at optimal level. Research for developing reliable framework for the collection of inter-organisational coordinated response data and its impact on decision-making and support system for disease outbreak is la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In 2014, Cui et al [20] demonstrated the public attention model for epidemics like H1N1 using spatial-temporal patterns. In 2014, Bdeir et al [21] discovered some of hidden social networks between different organizations during H1N1 epidemics. They also suggested that relevant and timely exchange of information between different organizations can result in better prevention of epidemics.…”
Section: Ict and Mathematical Models In H1n1 Epidemicmentioning
confidence: 99%
“…In 2014, Cui et al [20] demonstrated the public attention model for epidemics like H1N1 using spatial-temporal patterns. In 2014, Bdeir et al [21] discovered some of hidden social networks between different organizations during H1N1 epidemics. They also suggested that relevant and timely exchange of information between different organizations can result in better prevention of epidemics.…”
Section: Ict and Mathematical Models In H1n1 Epidemicmentioning
confidence: 99%
“…Bdeir et al 14 studied inter-organizational coordination during disease outbreaks and found that the main problem during disasters or emergency situations is that the coordination is not well controlled. Their study further argued that complexity arises when multiple agents interact with each other in a dynamic environment and that coordination is deemed necessary when a task needs to be completed through interdependent activities 14 . Similar situations occur in health organizations, which face coordination complexity in disease disaster because every disease outbreak seems unique by nature or symptoms or level of complexity.…”
Section: Coordination Of Detection Of Foodborne Disease Outbreaksmentioning
confidence: 99%
“…Thus, demand is high for an emergency response system to reduce the complexity in coordination. The question for researchers, practitioners, and policy makers is whether the standard top-down approach with its “hierarchal commands and control structure” successfully deals with high levels of complexity during disease outbreaks, 14 particularly if the outbreaks are caused by food contamination, or whether a new or complementary method (bottom-up approach) of coordinating complexity would have a much better success rate. This question remains almost unanswered in the literature.…”
Section: Coordination Of Detection Of Foodborne Disease Outbreaksmentioning
confidence: 99%
“…These roles and responsibilities most importantly apply to collaborative structures and coordination roles in the organizational network [811]. Second, in line with the need for clarity in collaborative structures and coordination roles, it is important to identify those network participants with the potential to play a brokerage or mediating role in the network [1215]. Network brokers have the potential to create an inclusive collaborative network and can facilitate the coordination in a network.…”
Section: Introductionmentioning
confidence: 99%